A New Era, New Strategies: Education and Communication Strategies to Manage Greater Access to Genomic Information - Lewis, Megan A. (The Hastings Center report, 2018)
As next-generation genomic sequencing, including whole-genome sequencing information, becomes more common in research, clinical, and public health contexts, there is a need for comprehensive communication strategies and education approaches to prepare patients and clinicians to manage this information and make informed decisions about its use, and nowhere is that imperative more pronounced than when genomic sequencing is applied to newborns. Unfortunately, in-person counseling is unlikely to be applicable or cost-effective when parents obtain genomic risk information directly via the Internet. As a rule, communication strategies should match how people are accessing health information. Today, many people can obtain health information in a variety of settings, including through direct-to-consumer services, via websites, and through other digital channels or settings. In response to these changes, new communication strategies need to be considered. Adopting a comprehensive communication model means understanding the multiple levels of influence experienced by parents and the clinicians who serve them. In addition, applying communication-science principles can help in addressing some key challenges to effectively communicating genomic information to parents.